The Impacts of combining climate finance with ODA on the volume of development finance - GEBREYESUS, Kalekristos Zerisenay (KDI School, 2017)
There is a general agreement that climate finance has to be scaled up to deal with climate change. However, there is stern disagreement between developed and developing countries in their views of climate finance and its management. Although UNFCCC and subsequent protocols clearly call for increased “new and additional” climate finance, there is no legal definition of what “new and additional” finance mean, and this has resulted in contending interpretations of the terms. Developing countries interpret “new and additional” as a source of money out of annual national budget and additional to existing ODA target of 0.7% of GNI. They also insist on separating climate change finance from ODA claiming that combining the two funds allow donor countries to divert resources from development finance to climate finance and thus decrease funds they receive for economic growth and development. Conversely, developed countries support merger of climate finance with OD but clearly lack common interpretation of the “new and additional” principle. This study examines the impact of combining climate finance with ODA on development finance. Due to unavailability of time series data for climate finance, the study systematically measures ODA percentage of GNI since 1960 and the proportion of climate finance in it. The study finds that the decade average ODA against share of GNI has decreased throughout the five studied decades while the proportion of climate finance in it increased. Based on this systematic measurement, the study concludes that combining ODA and climate finance decreases development finance developing countries receive.
Thesis(Master) --KDI School:Master of Development Policy,2017